Development of Electrode Deposition Methods for Scale-up of Dye Sensitized Solar Cells - Anies Mutiari; Wisnu Ananda; Pramujo Widiatmoko; Hary Devianto; Isdiriayani Nurdin; Adriaan Adriaan; Mhd Ridho Utomo; Hilham Zamriko Koto (Journal of Engineering and Technological Sciences, 2020)
This research studied the effect of electrode deposition method on the performance of dye-sensitized solar cells (DSSCs). Four deposition methods (bar coating, doctor blade coating, screen printing, and spray coating) were compared. For commercial production purposes, applicability of the methods to a scaled-up DSSC was studied. In order to minimize the production cost, commercial activated carbon was utilized as counter electrode. The experimental results showed that the doctor blade technique provided the best DSSC performance among the investigated methods. Based on the study of cell I-V characteristics, the photoelectric conversion efficiency of the DSSC with an electrode active area of 70 cm2 was significantly lower than with 5 cm2 despite using the same deposition method. The electrochemical characteristics of the cells were further studied using electrochemical impedance analysis.